THE USE OF SINGULAR VALUE DECOMPOSITION IN INVERSION PROBLEM - SITI MULYANI (NIM: 20107052); Pembimbing: Dr.Muchtadi Intan Detiena, ENENG
Solution for inversion problem could be represented to d = Am , and we could apply simple procedure to get the value of m from the observation data. For an s x t matrix A which represent a data, where s > t , generally such system has no solutions, an approach to get the solution could be performed by using singular value decomposition and generalized inverse value. The system is changed into a consistent linear equations so the best solution obtained, and m acquired trough M=A+d On the application, the pursue of m is performed in data fitting which is the result of measurement on tomography, by using singular value decomposition and generalized inverse value.